The challenge of advanced model-based FDIR for real-world flight-critical applications. (February 2018) - Zolghadri, Ali
Abstract: This paper aims at providing a brief perspective of advanced model-based Fault Detection, Identification and Recovery (FDIR) for aerospace and flight-critical systems. A number of practical key factors for designing credible technological options are emphasized. Such considerations are decisive for the survivability of the design during ground/flight Validation & Verification (V&V) activities. The views reported in this paper are based on lessons learnt and results achieved through actions undertaken with Airbus during the last decade. As an illustrative example, a model-based fault monitoring technique is presented which has reached level 5 on Technological Readiness Level scale under V&V investigations at Airbus.